1980
DOI: 10.1007/bf01851843
|View full text |Cite
|
Sign up to set email alerts
|

Early micro- and macro-angiopathy in the streptozotocin diabetic minipig

Abstract: Streptozotocin diabetes in the minipig constitutes an outstanding model for the study of diabetic angiopathies. Changes which are classified as macroangiopathy are evident after 6 months, while the first changes indicative of microangiopathy appear already after about 18 months. The degree of pronouncement of the microangiopathy depends on the duration and severity of the induced diabetes. These results constitute a cogent argument in favour of the "metabolic theory" of the development of diabetic microangiopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
2

Year Published

1981
1981
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 21 publications
1
16
0
2
Order By: Relevance
“…We documented that mean fasting plasma insulin concentrations were similar in 130 mg/kg STZ-diabetic pigs (mean, 9 mU/L; range, 1-38 mU/L) compared with normal pigs (mean, 5 mU/L; range, 2-10 mU/L). Normal fasting plasma insulin concentrations have been observed before in alloxandiabetic minipigs [47], but the studies with STZ-diabetic (mini)pigs showed fasting hypoinsulinemia [6][7][8]25,26,48]. As discussed previously [48], the discrepancy in fasting plasma insulin concentrations may be explained by different strain, age, and sex, but also by different betacell toxic compound (alloxan or STZ) and the way of STZ administration.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…We documented that mean fasting plasma insulin concentrations were similar in 130 mg/kg STZ-diabetic pigs (mean, 9 mU/L; range, 1-38 mU/L) compared with normal pigs (mean, 5 mU/L; range, 2-10 mU/L). Normal fasting plasma insulin concentrations have been observed before in alloxandiabetic minipigs [47], but the studies with STZ-diabetic (mini)pigs showed fasting hypoinsulinemia [6][7][8]25,26,48]. As discussed previously [48], the discrepancy in fasting plasma insulin concentrations may be explained by different strain, age, and sex, but also by different betacell toxic compound (alloxan or STZ) and the way of STZ administration.…”
Section: Discussionmentioning
confidence: 90%
“…Because lipoprotein and lipid metabolism in humans and pigs are very alike [3,4], it may be expected that streptozotocin (STZ) treatment for pigs (ie, the chemical induction of diabetes) can create a type 2-like diabetic pig model with regard to insulin resistance, glucose homeostasis, dyslipidemia, and the response to oral anti-type 2 diabetes mellitus drug therapy. Streptozotocin, a chemical agent that damages pancreatic beta cells, has frequently been used to induce insulin-deficient diabetes in many species [22][23][24][25], and depending on the dose and strategy of STZ administration, a type 1-like [7,26,27], or a type 2-like [28][29][30][31], diabetes mellitus can be generated. Rapid intravenous injection of STZ at doses of around 100 mg/kg or higher produces insulin-dependent diabetes in pigs within days after STZ administration, and diabetes remains present for periods up to 3 years [6,7,25,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantially increased fasting plasma glucose (FPG) levels and decreased insulin secretion in response to glucose stimuli have been obtained as well as increases in plasma triglycerides and total cholesterol (27,29). Late complications typical of diabetes, such as capillary basement membrane thickening and cataracts, have also been shown in diabetic minipigs (28,41).In other studies, alloxan has been used for induction of diabetes in pigs (11,25,41). This compound, which has ␤-cell-toxic properties similar to those of STZ, in a dose of 200 mg/kg in Yucatan minipigs induced severe diabetes with high mortality due to hypoglycemia following acute hyperinsulinemia as a consequence of massive ␤-cell damage (41).…”
mentioning
confidence: 91%
“…Due to the anatomical, physiological, and metabolic similarities with human body, mini-pigs are considered as a suitable model in biomedical research. 24 The common blood biochemical index of mini-pigs and the absorption, transfer, and utilization of glucose are also similar to the corresponding processes in humans. 25 Thus, mini-pigs can be considered a valuable model for observing bone remodeling and the interaction between bone and implants under the impact of diabetes.…”
mentioning
confidence: 81%